Moldova's parliamentary elections of November 2014. (December 2015) - Brett, Daniel; Knott, Eleanor
Highlights: Ruling pro-European parties and long-established Communist Party lost significantly. Moldova's Socialist Party were the biggest winner. The elections concern more than ethnic and geopolitical cleavages. Endemic corruption is harming established parties' reputation and electability. Moldova's elections demonstrate continued electoral and institutional volatility.